Telerehabilitation—A Viable Option for the Recovery of Post-Stroke Patients - Viorela Mihaela Ciortea (MDPI AG, 2021)
As the number of stroke survivors is continuously growing, with an important number suffering from consequent functional deficits, the rehabilitation field is facing more complex demands. Technological progress gives us the opportunity to remotely assist patients while they exercise at home through telerehabilitation (TR), addressing the problems of limited medical resources and staff, difficult transportation, or living a long distance from rehabilitation centers. In addition, TR is a way to provide continuity in long-term post-stroke recovery during the COVID-19 pandemic, which limits traveling and human interaction. While the implementation of TR is increasing, the biggest challenges are to raise patients’ acceptability of the new method and their motivation and engagement during the program. In this review, we aimed to find methods to address these challenges by identifying the patients who benefit the most from this therapy and efficiently organizing the space and technology used for telerehabilitation. User-friendly technologies and devices along with therapists’ constant support and feedback are some of the most important aspects that make TR an efficient intervention and an alternative to conventional therapy.